Research on the Current Situation and Countermeasures of Protection and Utilization of Sichuan's Red Cultural Resources (Journal of humanities and social sciences exploratio, 2025)
Since the 18th National Congress of the Communist Party of China, the Party Central Committee with Comrade Xi Jinping at its core has stood at the strategic height of the great rejuvenation of the Chinese nation, frequently emphasizing the strategic need to make good use of red resources and inherit the red bloodline. It has also implemented systematic planning for how to inherit red culture in the new era. Sichuan Province is an old revolutionary base area that the Red Army passed through the widest area and the longest time during the Long March. It is not only a key area of the Sichuan-Shaanxi Revolutionary Base Area, but also contains a unique "genetic code" of red culture. It retains complete traces of the Long March spirit, and in the process of founding New China, it has given birth to many spiritual lineages such as the spirit of the "Third Front" construction, the spirit of "Two Bombs and One Satellite", and the spirit of earthquake relief, thus forming a red cultural matrix that transcends the limitations of time.Under the tide of history, Sichuan's red culture has been marked with distinct characteristics of the times: the snow-capped mountains and the Dadu River have built revolutionary monuments, the "Third Front" construction has laid a strategic foundation, the national defense miracles have been shocking, and the people have united as one in earthquake relief. Sichuan's red culture has always been in sync with the pulse of the times. This cultural form, which not only inherits the historical context but also bears new characteristics of the times, not only adds the spiritual quality of perseverance and dedication to Bashu culture, but also demonstrates unique value in the vivid practice of the "Two Combinations". It is a local symbol carrying the spiritual lineage of Chinese Communists. The inheritance and development of Sichuan's red culture will provide spiritual support for the construction of a culturally strong province, and also offer local wisdom for promoting the integration of the basic principles of Marxism with China's excellent traditional culture and the practice of socialist construction, demonstrating the vigorous vitality of red genes in the new era.
Keywords: Red culture; Sichuan's red culture; Inheritance and development; Countermeasures